2016
DOI: 10.1080/21658005.2016.1148964
|View full text |Cite
|
Sign up to set email alerts
|

Inter-linkage among some physico-chemical and biological factors in the tropical mangrove estuary

Abstract: The interaction between abiotic and biotic parameters in an ecosystem usually shows health and functioning of the system. Thus, some physico-chemical parameters, phytoplankton abundance, chlorophyll a and primary production of the mangrove estuary in Sarawak, Malaysia were extensively investigated from January 2013 to December 2013 in order to establish the inter-linkage among them. The Pearson correlation coefficient revealed a significant relation between atmospheric and water temperatures (r = 0.692). Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Generally, rainfall plays an important role in seasonal cyclic phenomena in the tropical environment, causing important changes in the hydrology of the estuarine environment. In the present study, rainfall showed a good connection with changes in salinity and water temperature in this estuarine system [65]. Our results indicate two broad patterns of change: the brackish water expanding moderately to upstream during the dry season and the freshwater habitat expanding to downstream during the wet season.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Generally, rainfall plays an important role in seasonal cyclic phenomena in the tropical environment, causing important changes in the hydrology of the estuarine environment. In the present study, rainfall showed a good connection with changes in salinity and water temperature in this estuarine system [65]. Our results indicate two broad patterns of change: the brackish water expanding moderately to upstream during the dry season and the freshwater habitat expanding to downstream during the wet season.…”
Section: Discussionsupporting
confidence: 73%
“…The rapid increase in human activity in the estuaries and coastal areas has increased the nutrient transport from land to sea in the past decades, resulting in environmental deterioration and changes to biogeochemical processes [64]. The quality of water is defined by its physical, chemical, and biological parameters, and all these characteristics directly or indirectly influence the survival and production of aquatic species [65]. The changes recorded in physico-chemical characteristics of the MRE clearly showed that the variability of the estuarine regime is mostly conditioned by seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, water temperature showed a significant positive correlation with salinity (r = 0.85), TDS (r = 0.86), and ammonia-nitrogen (r = 0.45) but significant negative correlation with DO concentration (r = -0.90). Saifullah et al, (2016) also showed a significant positive correlation of surface water temperature with TDS (r = 0.71), salinity (r = 0.74) and conductivity (r = 0.78) in the mangrove estuary in Sarawak, Malaysia. The spatial uniformity in surface water temperature in PRE has the least probability of affecting the plankton abundance and distribution.…”
Section: Water Quality Parametersmentioning
confidence: 84%
“…The lowest water temperature in January was due to the lowest atmospheric temperature and the higher temperature in April could be attributed due to higher solar radiation. Saifullah et al (2016) observed a significant positive correlation between temperatures of water and the atmosphere. Similar range of temperature between 19°C and 31.1°C has been reported by Rahman et al (2013) during the dry season in the Sundarbans mangrove river system in Bangladesh.…”
Section: Water Quality Parametersmentioning
confidence: 92%